Six-component synthesis and biological activity of novel spiropyridoindolepyrrolidine derivatives: A combined experimental and theoretical investigation - Hossaini, Zinatossadat; Mohammadi, Marziyeh; Sheikholeslami-Farahani, Fatemeh (Frontiers in Chemistry, 2022)
Petasites hybridus rhizome water extract was used as green media for the preparation of Ag/Fe3O4/CdO@multi-walled carbon nanotubes magnetic nanocomposites (Ag/Fe3O4/CdO@MWCNTs MNCs), and its activity was evaluated by using in the one-pot multicomponent reaction of isatins, acetyl chloride, secondary amines, vinilidene Meldrum’s acid, primary amines, and malononitrile in an aqueous medium at room temperature for the generation of spiropyridoindolepyrrolidine as new derivatives with tremendous output. In addition, organic pollutant reduction of 4-nitrophenol (4-NP) was carried out by generated Ag/Fe3O4/CdO@MWCNTs in water at room temperature. The results displayed that Ag/Fe3O4/CdO@MWCNTs were reduced as pollutants of organic compounds in a short time. The synthesized spiropyridoindolepyrrolidine has an NH2 functional group that has acidic hydrogen and shows high antioxidant ability. Also, the spiropyridoindolepyrrolidine exhibited antimicrobial ability, and the method that is used for this purpose is the disk diffusion method, and two kinds of bacteria, Gram-positive and Gram-negative, were employed for this analysis. Also, to better understand the reaction mechanism density, functional theory-based quantum chemical methods have been applied. For the generation of spiropyridoindolepyrrolidine, the used process has many properties such as reactions with short time, product with good yields, and simple extraction of catalyst from the mixture of reaction.